Work-based Learning for Pesantren Economic Development: Evidence from The Idrisiyyah Umrah and Hajj Travel Unit - Saepulah AM; Irfan Moch Noor; Toto Suharto; Fauzi Muharom (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2026)
This research aims to examine the Work-Based Learning (WBL) model as an instrument for developing economic independence in the Idrisiyyah Islamic Pesantren through its Umrah and Hajj Travel business unit. The study is motivated by the need for modern pesantren to achieve professional, sharia-compliant financial sustainability while functioning as vocational learning laboratories. Utilizing a descriptive qualitative approach, this research gathers data from final-year students, alumni, and managers acting as mentors through literature studies, institutional documentation, and direct field observations. The results demonstrate that approximately 35–45% of final-year students are actively engaged in operational activities, including administration, customer service, ritual guidance, and departure coordination. This hands-on involvement significantly enhances students' competencies across three main dimensions: technical (travel procedures), social (communication), and spiritual (Islamic service ethics). Furthermore, integrating WBL improves service professionalism via standardized SOPs, strengthens congregational trust, and expands digital marketing reach. The travel unit also generates job opportunities for alumni and provides internal competency recognition for the participating students. This study concludes that the travel business unit functions not only as a revenue source for the pesantren but also as a structured, sustainable work-based vocational education system that effectively integrates economic functions with traditional religious education.